Filicopsida from the lower Westphalian (Middle Pennsylvanian) of Nova Scotia and New Brunswick, Maritime Provinces, Canada - Álvarez-Vázquez, Carmen (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2019)
This paper presents a taxonomic revision of filicopsid taxa from the lower to middle Westphalian strata of Nova Scotia and New Brunswick, Maritime Provinces of Canada. Most of the material represents sporadic historical collecting by Geological Survey of Canada (GSC) personnel, and specimens are in the GSC collections in Ottawa. Additional specimens are in the New Brunswick Museum at Saint John, the Fundy Geological Museum at Parrsboro, and the Joggins Fossil Institute at Joggins. Two specimens from outside Canada clarify specific characteristics. The revision involved the detailed examination of 20 adpression (mainly impression) taxa, of which one, Germera brousmicheae, is new. Detailed synonymy lists, with particular focus on records from Canada and the USA, facilitate a refinement of the stratigraphic and geographic distribution of these species. Most of the taxa from the Maritimes are the same as those from other parts of the paleoequatorial belt of Pennsylvanian times. The Maritimes record of filicopsid taxa closely resembles the filicopsid floras of western Europe, most notably the British Isles.